2015
DOI: 10.1021/acs.macromol.5b00564
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Fluorine onto Different Positions of Phenyl Substituted Benzo[1,2-b:4,5-b′]dithiophene Unit: Influence on Photovoltaic Properties

Abstract: We have designed and synthesized two low bandgap conjugated copolymers containing alternating meta-fluoro-p-alkoxyphenyl-(m-FPO-) or p-fluoro-m-alkoxyphenyl-(p-FPO-) substituted benzodithiophenes-co-benzooxadiazole (BO), named PBO-m-FPO and PBO-p-FPO. The properties, including UV−vis absorption, charge mobility and photovoltaic performance of the two polymers have been intensively investigated. The results indicated that the introduction of fluorine atom at m, p positions of phenyl substituted benzodithiophene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 56 publications
0
27
0
Order By: Relevance
“…6 It is well-known that low band gap polymers with high V oc are crucial to attaining the objective of high performance PSCs. [8][9][10][11][12][13][14][15][16][17][18][19][20] Due to the strong electronwithdrawing characteristic of the uorine atom, the introduction of F as a substituent to the conjugated polymer would lower both energetic positions of the HOMO and LUMO levels of the synthesized polymer, as demonstrated by Brédas et al in a theoretical study. However, adding electron-withdrawing groups to the polymer can generally lower the energetic position of the LUMO level.…”
Section: Introductionmentioning
confidence: 99%
“…6 It is well-known that low band gap polymers with high V oc are crucial to attaining the objective of high performance PSCs. [8][9][10][11][12][13][14][15][16][17][18][19][20] Due to the strong electronwithdrawing characteristic of the uorine atom, the introduction of F as a substituent to the conjugated polymer would lower both energetic positions of the HOMO and LUMO levels of the synthesized polymer, as demonstrated by Brédas et al in a theoretical study. However, adding electron-withdrawing groups to the polymer can generally lower the energetic position of the LUMO level.…”
Section: Introductionmentioning
confidence: 99%
“…[16,17] Our previous work has shown that cofacialfluoroarene-arene (ArF-ArH) interactions of perfluorinated side chains can dictate the conformations and assemblies of phenylene-ethynylenes( PEs), and therefore determine their solid-state opticalp roperties. [18][19][20] Although examples exist for which regiochemistry of arene fluorination alters crystalp acking with modest effects on material properties, [21][22][23][24] slightd ifferences in fluorine regiochemistry of non-conjugated side chains would not generally be expected to impact the opticalp roperties of conjugated materials. Here, we describe surprisingly different opticala nd mechanofluorochromic (MFC) properties of solid PEs that depend on slight positional differences of Ha nd Fa toms (2,4,6v s. 2,3,6-trifluoro) on pendant arenes not conjugated to the PE moiety.…”
mentioning
confidence: 99%
“…To date, benzo(1,2‐b:4,5‐b')dithiophene (BDT), as a backbone building block to construct donor polymers, has received considerable attention because of its large planar structure and excellent photovoltaic performance in PSCs . The side chains flanking on the two‐dimensional (2D) conjugated unit BDT, such as phenyl substituted BDT (BDTP) and thienyl substituted (BDTT), play an critical role not only in the solubility for polymer but also in their optical and electrical properties . Compared with the two building blocks, the weaker electron‐donating nature of BDTP has relatively lower HOMO energy levels, which has been used to effectively lower the polymer energy levels than thienyl substituted BDTT unit .…”
Section: Introductionmentioning
confidence: 99%